Students’ Speaking Difficulties in Learning Descriptive Text in Grade 10 Students at SMA Muhammadiyah 1 Surakarta - Salsabila Azzalia; Rini Fatmawati (CV. Pusdikra Mitra Jaya, 2026)
EFL students often exhibit passivity, hesitation, and low confidence when required to speak English, particularly during descriptive text instruction. Therefore, this study aims to identify the types of speaking difficulties and analyze the underlying factors influencing these challenges among tenth-grade students at a private Islamic senior high school in Surakarta. This research employs a qualitative approach, utilizing classroom observation, semi-structured interviews, and document analysis for data collection. The results indicate that students face difficulties in four main aspects: grammar, vocabulary, pronunciation, and speaking fluency, with limited vocabulary being the most dominant barrier. Additionally, these difficulties are significantly influenced by a combination of psychological, linguistic, and environmental factors, where psychological issues namely anxiety and low self-confidence act as the primary triggers for students' lack of fluency. In conclusion, speaking difficulties in learning descriptive texts stem from a complex interaction of psychological, linguistic, and environmental variables. The implication of this study is that educators must implement comprehensive instructional strategies that not only focus on linguistic competence but also actively build a supportive learning environment to reduce student anxiety.